PRODUCTIVITY OF WATER AND FERTILIZER USE IN FERTIGATED CARROT CULTIVATION - Da Silva, Julianna Catonio; Dos Santos, Daniella Pereira; Teodoro, Iêdo Peroba De Oliveira; Da Silva, Thaís Rayane Gomes [UNESP]; De Menezes, Sirleide Maria; Dos Santos, Márcio Aurélio Lins (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
Aiming at the optimization of the management of production factors, an experiment was carried out to evaluate the effect of irrigation depths and fertilizer doses on the productivity of water and fertilizer use in fertigated carrot cultivation. The experiment conducted in the experimental area of UFAL, Arapiraca, presented a randomized block design, in a 6x4 factorial scheme, three replications. The treatments were six irrigation depths: L1: 210.5; L2: 315.7; L3: 421.0; L4: 526.2; L5: 631.5; and L6: 736.7 mm and four doses of fertilizer: F1: 226.9; F2: 340.3; F3: 453.8; and F4: 567,2 kg ha-1 applied via fertigation. At the end of each cycle, four carrot/parcel roots were collected to estimate productivity. The combination of irrigation depth and fertilizer dose that obtained the highest water productivity (24.3 kg m-3 ) was 293.46 mm and 553.74 kg ha-1, respectively. The maximum fertilizer productivity (345.36 kg-1 ) was obtained by applying 226.89 kg ha-1 of fertilizer and an irrigation depth of 517.50 mm. The productivities of water and fertilizer use increased as irrigation depths and fertilizer doses were reduced, respectively.
PRODUTIVIDADE DO USO DE ÁGUA E FERTILIZANTE NO CULTIVO DA CENOURA FERTIRRIGADA
Keywords: Daucus carota; irrigation depth; mineral nutrition; production efficiency